Teaching Students Pronunciation Skills through Tongue Twister Exercises - Rahman Hakim; Pupun Sampurna (Journal of English Language Teaching and Cultural Studies, 2020)
This study discusses about the teaching of English pronunciation practices to the students of Early Childhood Education Study Program of Faculty of Teacher Training and Education of Universitas Sultan Ageng Tirtayasa. This study was qualitative research which carried out in the learning of the English Education for Early Childhood subject of Early Childhood Education Study Program of Faculty of Teacher Training and Education of Universitas Sultan Ageng Tirtayasa. The researchers chose tongue twisters as the material used to train students' ability to pronounce their vocabularies in English. The result shows that tongue twister exercises can improve their English vocabulary pronunciation skill; and their abilities to pronounce every vocabulary will be stored in the child's memory and become the main standard in the next learning process.